"Call for the Use of Axial Terms": Toward Completeness of NANDA‐I Nursing Diagnoses Labels. Issue 3 (18th October 2018) - Miguel, Susana; Romeiro, Joana; Martins, Helga; Casaleiro, Tiago; Caldeira, Sílvia; Herdman, T. Heather
Abstract : PURPOSE: This article explores the current structure of NANDA‐I nursing diagnoses (ND) labels. METHODS: Critical analysis of the ND labels, as categorized in the NANDA‐I terminology. FINDINGS: Most of the 244 ND labels are composed of terms from the focus and judgment axes. CONCLUSIONS: The specificity of the human responses toward health and life transitions may not be totally represented in the two most common axes, as categorized within taxonomy II. IMPLICATIONS FOR NURSING PRACTICE: Improvements in NANDA‐I diagnosis labels would contribute to an advanced terminology and to increased specificity and accuracy of the diagnostic process that is needed in clinical practice. Completeness of the ND labels would reflect clinical reasoning preciseness and help students and nurses in delivering more personalized, safe, and effective patient‐centered care. OBJETIVO: Este artigo explora os títulos dos diagnósticos de enfermagem da NANDA‐I. MÉTODOS: Análise crítica dos títulos dos diagnósticos de enfermagem da NANDA‐I. RESULTADOS: A maioria dos 244 diagnósticos de enfermagem classificados são compostos essencialmente por termos referentes ao foco e ao julgamento. CONCLUSÕES: A especificidade das respostas às transições de saúde e vida pode não estar totalmente representada nos dois eixos mais comuns, como apresentado na taxonomia II. IMPLICAÇÕES PARA A PRÁTICA: Melhorias nos diagnósticos da NANDA‐I em relação ao seu aspeto multiaxial contribuiriam no desenvolvimento da sua terminologia e poderiam melhorar a especificidade e acurácia do processo diagnóstico que é necessário à prática clínica. Complementar os títulos dos diagnósticos de enfermagem poderia refletir a acurácia do raciocínio clínico e ajudar os estudantes e enfermeiros em prestarem cuidados centrados no paciente mais personalizados, seguros e eficazes.